Improving Sales Pipeline Management - Břešťan, Jaroslav (2023)
Effective and systematic sales pipeline management is key for successful sales operations. Unfortunately, there are some indications that Siemens Digital Industries might have issues with their sales pipeline management, as their sales pipeline has become unreliable and unpredictable. Therefore, the aim of this thesis is to thoroughly examine the sales process at Siemens Digital Industries and identify issues connected with their sales pipeline and sales pipeline management. Consequently, based on these findings, propose improvements which will better the current situation and will lead to more successful sales operations at Siemens. The inputs for this thesis were collected through an extensive literature review and internal investigation at Siemens Digital Industries (DI). This investigation mainly involved in-depth interviews with all sales managers and selected sales representatives. In summary, it was confirmed that DI has an ineffective sales pipeline management with numerous issues connected with sales measures and data quality of the sales pipeline. The business framework and BI solution was proposed based on the identified issues combined with findings from the literature review. The business framework aims to improve sales operations at DI through the improvement of sales pipeline management. The proposed BI solution should support this change initiative and help sales managers to promote this change in the sales organization. After the successful implementation of the business framework and deployment of the BI solution, the sales pipeline’s data quality improvements were observed. Nevertheless, further research and testing is necessary for confirmation of their functionality and contribution to the sales pipeline management and consequently to sales operations.